Development of a direct (non-extracted) enzyme immunoassay for measurement of serum progesterone levels in mares - Brooks, Ryan Michael, author; Denniston, David, advisor; Bruemmer, Jason, committee member; Nett, Torrance, committee member; McCue, Patrick, committee member (Colorado State University. Libraries, 2010)
Progesterone (P4) is a steroid hormone produced by the corpus luteum of the ovary and the placenta of the mare. Progesterone is required for the maintenance of pregnancy and an assessment of endogenous concentration would be useful in many diagnostic applications related to equine breeding management. The overall objective of this study was to develop and validate a direct enzyme-linked immunosorbent assay (ELISA) for the measurement of P4 in serum of in the mare. The specific aims were as follows: 1) to develop a quantitative and sensitive progesterone assay that could be used for non-extracted equine serum or plasma, and 2) to convert the ELISA from a 96-well plate format to a single cuvette system to allow quantification by a commercially available spectrophotometer. Significant events in the successful development of the ELISA included the use of purified anti-progesterone antibody, heterologous combination of antibody and conjugate, use of TMB substrate, and methodology to avoid organic solvent extraction. It was determined that by lowering the volume of serum used in the assay and lowering the pH of the serum, the need for extraction could be avoided. The overall correlation between ELISA of non-extracted serum and radioimmunoassay (RIA) of extracted serum was high (r = 0.81); and the correlation between ELISA and RIA for progesterone concentrations less than 5.0 ng/ml, the range most important for clinical diagnosis, was even greater (r = 0.91). The direct ELISA assay has great potential for use in the equine breeding industry as it will allow for diagnostic tests to determine the adequacy of corpus luteum function in a pregnant mare, presence or absence of luteal tissue, and assessment of the end of seasonal transition.
Keywords: Horses -- Reproduction; Mares; Progesterone; Enzyme-linked immunosorbent assay